Recurrent PIK3CA H1047R-Mutated Congenital Infiltrative Facial Lipomatosis: A Case Report and Review of Literature - Kei Shing Oh; Hisham F. Bahmad; Kalin Veselinov Stoyanov; Ibrahim H. Amjad; Carole Brathwaite (Current Issues in Molecular Biology, 2023)
Congenital infiltrating lipomatosis of the face (CILF) is a rare, congenital, nonhereditary facial overgrowth due to post-zygomatic activating mutations in PIK3CA gene. It is unilateral and involves hypertrophy of both the soft and hard tissue structures on the affected side of the face. This commonly results in early eruption of the teeth, hypertrophy of the facial bones, macroglossia, and proliferation of the parotid gland. Less than 80 cases of CILF have been reported in the literature so far. Treatment modalities include liposuction and surgical excision. However, since the hallmark of CILF is mutation in the PIK3CA gene, PI3K inhibitors may play a therapeutic role in CILF. We report a case of an 8-year-old boy with recurrent CILF of the scalp and nose, with PIK3CA H1047R mutation. We discuss the differential diagnoses, clinical outcomes, and management of this rare entity.